PENGARUH KOMPETENSI ETOS KERJA PETUGAS TERHADAP KEPUASAN PASIEN DI KLINIK FISIOTERAPI RSUD DATU BERU TAKENGON KABUPATEN ACEH TENGAH TAHUN 2019 - Asmarani Yusnita Ida Sirait; Arifah Devi Fitriani; Masnelly Lubis (STIKes Hang Tuah Pekanbaru, 2020)
Abstract Health has become a basic need for the community. This study aims to analyze the effect of the competence of the work ethic of officers on patient satisfaction. This type of research is Analytic Survey with Cross Sectional Study approach. The instrument used was a questionnaire sheet that was distributed to 60 respondents in an analysis with multiple logistic regression tests. The results of data analysis showed that there was an influence on patient satisfaction, namely the disciplinary variables, the accuracy of the officers and the responsibilities of the officers with a value of p (sig) = <0.05. The most dominant variable that has an influence on patient satisfaction is the accuracy of the officer with p (sig) 0,002 and has an OR value of 13,360. The conclusion of this research is that there is a relationship between the competence of the work ethic of the officers in terms of discipline, honesty, accuracy, responsibility, and emotional maturity of the physiotherapist's staff to patient satisfaction. Suggestions increase discipline, honesty, accuracy, responsibility, and emotional maturity so that patients are satisfied in receiving the physiotherapy services provided.